Sharing Session pada Kegiatan Immersion sebagai Wadah Pertukaran Pengetahuan Kewirausahaan - Triyanti, Vivi; Lembana, Devi Angrahini Anni (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2024)
An immersion is an intensive activity in which participants are fully involved in a particular environment or context for a short or limited period of time. In the entrepreneurship immersion arranged by Atma Jaya Incubator Business, one of the activities is a sharing session which is a presentation of material and discussion between Atma Jaya Catholic University of Indonesia (Unika Atma Jaya) and Universiti Teknologi Malaysia (UTM) students. There were three keynote speakers from Atma Jaya and UTM who provided material, The three speakers shared about the use of technology in developing entrepreneurship in both countries, as well as sharing about the use of technology in various community service activities in Unika Atma Jaya. This sharing session activity had a positive impact in increasing students' knowledge, both regarding entrepreneurship and the culture of entrepreneurship from both countries.